Efficacy of a comprehensive strategy for the detection and treatment of hepatitis C infection in a population attending addiction centers - Corona-Mata, Diana; Rivero-Juárez, Antonio; Camacho, Ángela; Ruiz-Torres, Laura; Ruiz-Cáceres, Inmaculada; de la Fuente Darder, Bartolomé; Cáceres-Anillo, David; de Guía Castro-Granados, María; Lizaur-Barbudo, María; Victoria Cabrera-Gisbert, María; Redondo-Écija, Justa; Aparicio-Aparicio, Ana; et al. (Frontiers in Public Health, 2023)
Background & Aims: The burden hepatitis C infection in people with history or current drug use suppose a high risk of hepatic complications and transmission infectious disease. This population is poor linked to heath system and is difficult to achieve them and support treatment because they have high rates of lost follow-up. Our aim was to evaluate an intervention for the diagnosis and treatment of chronic hepatitis C and HIV in this population. Methods: Six-hundred and eighty-three people attended in Drugs and Addictions Centres (DAC) were asked to participate in health counselling and provide blood sample for test HCV, HIV, and syphilis from April 2019 to June 2020. Totally 556 subjects were surveyed and tested. All of them were assigned to a patient navigation program to improve health education and linking to the sanitary system. Hepatitis C infection patients were evaluated in an ampliated medical consult to evaluate hepatic stage with transient liver elastography and initiated Direct Acting Antivirals to achieve Sustained Viral Response. Results: Of the 556 patients who agreed to participate in the study, 33 (5.9%) had active HCV infection. Of the 33 patients infected with HCV, 3 were lost to follow-up once the diagnosis of HCV infection was made. Twenty-eight patients (93.3%) completed treatment and 26 achieved Sustained Viral Response (78.8%). Of the 30 patients, seven (23.3%) had advanced fibrosis, and of these, four (16.6%) had liver cirrhosis. One of the cirrhotic patients had hepatic space-occupying lesions at the baseline evaluation and was diagnosed with hepatocarcinoma. Conclusions: Our study suggests that the implementation of strategies based on personalized intervention models can contribute to the control of HCV infection in DAC users.